The IGF Hormonal Network in Endometrial Cancer: Functions, Regulation, and Targeting Approaches - Bruchim, Ilan; Sarfstein, Rive; Werner, Haim (Frontiers in Endocrinology, 2014)
Epidemiological as well as clinical and experimental data identified the insulin-like growth factors (IGF1, IGF2) as important players in gynecological cancers in general, and endometrial tumors in particular. The IGF1 receptor (IGF1R), which mediates the proliferative and anti-apoptotic activities of both ligands, emerged in recent years as a promising therapeutic target in oncology. However, most clinical trials conducted so far led to mixed results, emphasizing the need to identify biomarkers that can predict responsiveness to anti-IGF1R targeted therapies. This article will review recent data regarding the role and expression of IGF system components in endometrial cancer. In addition, we will review data on the interplay between the IGF signaling pathway and tumor suppressors p53 and BRCA1. Antioncogenes p53 and BRCA1 play a key role in the etiology of gynecological cancers and, therefore, their interaction with IGF1R is of high relevance in translational terms. A better understanding of the complex mechanisms underlying the regulation of the IGF system will improve our ability to develop effective treatment modalities for endometrial tumors.